(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
2008 has been the year of the accession of Technologies of the Information (IT) innovative of impact in the economy, the business and the society in general: Web 2.0, which one began to spread for Tim O’Reilly in 2004 and already it is a palpable reality, Semantic Web promoted by Tim Berners-Lee -the father of the Web- andreflected in the semantic seekers increasingly near; Web 3.0 like convergence of the Web 2.0 and the Semantic Web. The new Web new technological models have brought: Software as a Service, Virtualization and Storage Web These models have brought a new technological, economic and social paradigm: The Cloud Computing.The article analyzes the advantages and risks for the users, organizations and companies of the adoption of this new platform or architecture web, as well as the way makes opened for one more analysis in depth of the nascent Enterprise 2.0. Also itis alerted on the great social risk that there bring these technologies “The possible endof the privacy".